Penanggulangan Gelandangan Pada Jabatan Kebajikan Negeri Kedah Malaysia Melalui Layanan Konseling Islam - Nurul Husna Binti Abd Malek; M. Fahli Zatrahadi (Madania: Jurnal Ilmu-Ilmu Keislaman, 2020)
This research is based on the assumption that the rise of homeless and beggars in the City of Alor Setar. This condition has caused disrupt the beauty and comfort of the city as a result of cancer suffered by the city and the State. For this reason, the government through the Kedah Community Virtue Position has built a transit house as a temporary stopover place for which they are then given guidance on Islamic counseling. Based on the facts above, this study answers the problem formulation, namely how to guide Islamic counseling in tackling homelessness in the City of Alor Setar by the Office of Benevolent Society of the State of Kedah, Malaysia. To answer these questions, this study uses descriptive qualitative methods.This study aims to describe the techniques of Islamic Counseling Guidance conducted by Counselor officers in counseling activities carried out by counselors from the Department of Public Virtue to the homeless in the City of Alor Setar. This research is a qualitative research, namely a type of field research field research, the nature of descriptive research, this study uses interview, observation, and documentation data collection techniques. Interviews were conducted with counselors and midfielders who had participated in Islamic counseling activities in the City of Alor Setar Negeri Kedah Darul Aman, Malaysia. Observation was carried out Islamic counseling guidance techniques used and the process of Islamic counseling in the Office of Benevolence of the Community of Kedah Darul Aman, Malaysia. Photo documentation of Islamic counseling activities. The data source of this research is primary data and secondary data. Qualitative data analysis with deductive deduction method. From the results of this study the Islamic counseling process in the public virtue  position using three homeless people can follow the stages of counseling well so that the homeless can be firm in his faith, especially mental and mental health, can control themselves and understand what is ordered and forbidden by Allah SWT so that when the homeless people have come out to the outside community they no longer feel inferior and can also adjust to society.